Problems of the definition of corporate reporting - N. V. Malinovskaya (Учёт. Анализ. Аудит, 2022)
In recent decades, there has been a general trend aimed at the development and introduction of new types of reporting into the management practice. These methods were based on a different conceptual framework than financial statements, changing the perception of corporate reporting and its target orientation. There has to be streamlined the conceptual and categorical apparatus which is necessary for building a corporate reporting system. The aim of the study is to identify and systematize approaches to the definition of corporate reporting in order to determine the role and place of various types of statements in the corporate reporting system. There were used bibliometric analysis, general scientific methods of cognition, such as analysis, synthesis, generalization, abstraction, and a systematic approach. There were established the dynamics of scientific publications based on the bibliometric analysis which had been posting on the eLibrary. Ru platform for the period 2000–2021 by the keyword “corporate reporting”. Approaches to the definition of the term “corporate reporting” are generalized and systematized, based on the target of corporate reporting, the composition of the components included in the corporate reporting system. There were identified factors influencing the transformation of the corporate reporting concept and considered its possible formats. The definition of corporate reporting was clarified based on the main essential characteristics of reporting. It is proposed to conduct further scientific research and discussions to develop a common approach to the definition of the term “corporate reporting”, as well as to the definitions of other types of reporting included in the corporate reporting system with the intention of development of its institution in Russia.